The tomb of the martyr Muhammad Baqir al-Sadr between attempts to obliterate and reveal, 1980-2003 - محمد الجزائري (آداب الكوفة, 2012)
The name of the martyr Muhammad Baqir al-Sadr was associated with the history of Islamic action in Iraq during the second half of the twentieth century. And lofty and penetrating into the hearts until it became a title for the course of Islamic and political reference work in Iraq.